Overcoming the Fear of Speaking English - Nuriddinov Najmiddin Nurvali o’g’li, Vaisboeva Barno Vaisboevna (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
Fear of speaking English is a common challenge among non-native speakers, especially in academic and professional settings. This fear often stems from a lack of confidence, fear of making mistakes, limited vocabulary, and anxiety about being judged by others. The aim of this paper is to explore the causes of this fear and present practical strategies to overcome it. These strategies include building a strong vocabulary, practicing with supportive peers, engaging in regular speaking exercises, and developing a growth mindset. The study also highlights the importance of creating a positive and encouraging learning environment. By implementing these approaches, learners can gradually increase their confidence, reduce anxiety, and become more effective English speakers.